Opioid prescribing patterns within otolaryngology - Alexander W. Murphey (KeAi Communications Co., Ltd., 2019)
Objective: Determine current opioid prescribing patterns for adult procedures within an academic Otolaryngology-Head and Neck Surgery training program in order to establish a general guideline and more uniform approach to narcotic prescribing practices. Methods: The is a prospective, single-center pilot study. An online, anonymous survey was sent to all members of the Otolaryngology-Head and Neck Surgery training program at Medical University of South Carolina including residents, fellows, and attending surgeons, and advanced practice providers (APP). The survey consisted of questions including demographics, most commonly prescribed analgesic and the average number of opioid tablets prescribed post-operatively for eleven of the most common adult procedures within Otolaryngology. Results: Forty-two participants responded to the survey. Of the 42 respondents, 20 were attending surgeons, 11 junior level residents (year 1–3), 6 senior level residents (year 4–5), and 5 A.P.P.s. The most commonly prescribed narcotic was hydrocodone-acetaminophen with 83.3% (35/42) of respondents prescribing this medication. Tonsillectomy or uvulopalatopharyngoplasty had the highest average number of tablets prescribed at 32.3 (Range: 5 to 90). Neck dissection, parotidectomy, and thyroidectomy procedures all averaged over 20 tablets. Direct laryngoscopy opioid dose was the lowest at 4.8 tablets (range 0–20). Opioid prescriptions by surgery were broken down by provider class with only septoplasty showing a significant difference with attending physicians prescribing an average of 20 tablets vs 14.1 tablets for residents (P = 0.034). Conclusion: We believe there remains an unacceptably high variability in current opioid prescribing patterns within otolaryngology especially within more painful procedures. Establishment of standardized post-operative narcotic guidelines is warranted. Keywords: Opioids, Narcotics, Otolaryngology